2016
DOI: 10.1115/1.4032240
|View full text |Cite
|
Sign up to set email alerts
|

Exergy, Energy, and Gas Flow Analysis of Hydrofractured Shale Gas Extraction

Abstract: The objectives of this study are to (a) evaluate the exergy and energy demand for constructing a hydrofractured shale gas well and determine its typical exergy and energy returns on investment (ExROI and EROI), and (b) compute the gas flow and intrinsic exergy analysis in the shale gas matrix and created fractures. An exergy system analysis of construction of a typical U.S. shale gas well, which includes the processes and materials exergies (embodied exergy) for drilling, casing and cementing, and hydrofractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…It has obviously made a tremendous contribution to China's oil industry and has maintained a long-term stable yield. Compare EROI POU of China's conventional fossil fuels with EROI of unconventional fossil fuels [34][35][36][37][38][39][40][41] from another country, it can be seen that the EROI for China's conventional fossil fuels is lower than the EROI of unconventional fossil fuels based on current literature. Figure 6 also shows the EROI of U.S. shale oil & gas and China's conventional oil & gas.…”
Section: Resultsmentioning
confidence: 99%
“…It has obviously made a tremendous contribution to China's oil industry and has maintained a long-term stable yield. Compare EROI POU of China's conventional fossil fuels with EROI of unconventional fossil fuels [34][35][36][37][38][39][40][41] from another country, it can be seen that the EROI for China's conventional fossil fuels is lower than the EROI of unconventional fossil fuels based on current literature. Figure 6 also shows the EROI of U.S. shale oil & gas and China's conventional oil & gas.…”
Section: Resultsmentioning
confidence: 99%
“…Kong et al [53] followed and computed the energy return of China domestic production of oil and gas, compared to their imports. Lior [54] determined the exergy and energy returns on investment of an hydro-fractured shale gas well. Wang et al [55] reviewed the physical supply and projections of EROI of fossil fuels in China, including natural gas.…”
Section: Eroi Of Gas At Local Regional or National Scalementioning
confidence: 99%
“…They analyzed gas turbine and solar collectors separately and results showed that the usage of collector in gas turbine leads to 64% fuel saving, but decreases by 2.8% electricity production. In 2016, Lior studied the exergy and energy analysis of hydro‐fractured shale gas. The study calculated the amount of exergy loss in each component and showed that exergy loss increases with time.…”
Section: Introductionmentioning
confidence: 99%